The Role of Organizational Communication in Improving the Performance of State Civil Apparatus - Dody Riyan Saputra; Mujahid Yunus; Andi Vita Sukmarini (Borong Newinera Publisher, 2026)
This study aims to determine the role of organizational communication in improving the performance of State Civil Apparatus (ASN) in the Mappakasunggu District, Takalar Regency, and to identify the obstacles that arise in improving the performance of State Civil Apparatus (ASN) in the Mappakasunggu District, Takalar Regency. The approach used in this study was descriptive with a qualitative approach. This study was conducted at the Mappakasunggu District Office, Takalar Regency from November to December 2025. The informants in this study were five. The results of this study indicate that organizational communication plays a very important role in optimizing the duties and responsibilities of State Civil Apparatus (ASN) as public servants. Through the flow of information, direction, and interaction between leaders and subordinates, organizational communication plays several important roles: an informative role, a performance motivation role, a role in building and strengthening cooperative relationships, and a communication role in providing services. Therefore, organizational communication plays an integral role in creating an efficient, collaborative, and creative work environment for Civil Servants (ASN) at the Mappakasunggu District Office. Barriers to the role of organizational communication in improving Civil Servants (ASN) performance include ineffective communication, differences in personality and experience, and inadequate resource constraints. These barriers can hinder the smooth flow of information, reduce Civil Servants' motivation, and hinder the achievement of organizational goals and optimal public service.